Factors that influence intention to adopt fragrant rice variety among rice supply chain players in Malaysia - Jamal, Kasazlinda (2019)
Malaysia depends almost exclusively on imports of fragrant rice mainly Basmati type from Pakistan and India. The import of this specialty rice showed a growing trend every year with a value of RM500 million. A new rice variety namely MRQ74 or also known as Mas Wangi that has 80% similar attributes to Basmati type has been innovated by the Malaysian Agricultural Research and Development Institute (MARDI). In 2011, fragrant rice farming was introduced under a new Entry Point Project 9 (EPP 9) for non-granary areas with the introduction of MRQ74 variety to take advantage of the higher-end rice market. However, fragrant rice production requires a comprehensive workflow to guarantee the quality of fragrant rice during planting, harvesting, and milling. All those players involved in the fragrant rice production must work together to reduce uncertainty in the supply chain and ultimately to ensure success and sustainable fragrant rice industry in Malaysia. Therefore, the general objective of this study was to determine the factors that influence adoption intention of the new rice variety, MRQ74 among the players within the rice supply chain. The approach of this study was conducted through a quantitative method. The conceptual framework of the study was developed by integrating seven (7) constructs namely relative advantage, low complexity, compatibility, market demand, government support, attitude, and intention to explain the behavioral intentions among farmers, millers, and wholesalers. The study involved four (4) different categories of rice supply chain players which represented by adopters (farmers) and non-adopters (farmers, millers, and wholesalers). The cross-sectional studies were conducted to gather data using four different sets of the questionnaire through various approaches. Face-to-face interviews were carried out to gather data from farmers, while for millers and wholesalers, data were collected through telephone, online, and postal surveys. The study involved 492 rice supply chain players, 70 adopters and 422 non-adopters that were chosen based on cluster random sampling technique. Descriptive analysis and factor analysis were conducted to analyze the data. Finally, the research models were analyzed with partial least square estimation approach (PLS-SEM) using Smart-PLS 3.0 software to validate the measures developed and verify the potential relationship among constructs. The predictors namely relative advantage, government support, and attitude were significantly influenced adopters’ continuance intention in adopting fragrant rice farming with 67.0% of the variance in intention. The result has proved that relative advantage was the strongest determinant factor and had the largest effect size for the adopters’ continuance intention in adopting fragrant rice farming. Moreover, the findings of the non-adopters (farmers) also found that government support, relative advantage, attitude, and market demand were significantly affected farmers’ intention in converting to fragrant rice farming with 47.4% of the variance in intention. The two factors namely relative advantage and government support were the most critical predictors that could motivate and convince farmers to adopt fragrant rice farming. Whereas, results from millers and wholesalers were different because relative advantage did not have a significant effect on their adoption intention. The results suggested that millers and wholesalers were not interested in adopting MRQ74 variety even though the benefits of the innovation were greater compared to the existing rice varieties. Further, the constructs namely attitude, government support, and relative advantage weakly explained 31.5% of the variance in millers’ intention and 28.9% of the variance in wholesalers’ intention. This study demonstrated that attitude was the primary determinant of rice supply chain players’ behavior, particularly for the millers and wholesalers. Besides, the favorable attitude of the rice supply chain players towards fragrant rice farming was influenced by innovation attributes namely relative advantage, government support, and market demand. The mediating analysis revealed that adopters’ attitude mediates the relationship between predictors (relative advantage, government support) and intention. Meanwhile, non-adopters (farmers) attitude mediates the relationship between predictors (market demand, government support) and intention. This study has provided further insights into the adoption intention research. Besides, this study explained the relationship between attitude and intention of adopting fragrant rice farming, as well as the relationship of other factors namely relative advantage, government support, and market demand. The results may be valuable for the policymakers to strategize actions to enhance the participation of the rice supply chain players in fragrant rice farming such as providing substantial support and incentives in the fragrant rice industry as well as educate rice players with updated information regarding the MRQ74 variety. This is to ensure the sustainability and competitiveness of the fragrant rice industry in Malaysia.